Preparation of nano-TiO2/diatomite-based porous ceramics and their photocatalytic kinetics for formaldehyde degradation - Gao, Ru-qin; Sun, Qian; Fang, Zhi; Li, Guo-ting; Jia, Meng-zhe; Hou, Xin-mei (International journal of minerals, metallurgy and materials, 2018)
Diatomite-based porous ceramics were adopted as carriers to immobilize nano-TiO2 via a hydrolysis-deposition technique. The thermal degradation of as-prepared composites was investigated using thermogravimetric–differential thermal analysis, and the phase and microstructure were characterized by X-ray diffraction, Fourier transform infrared spectroscopy, and transmission electron microscopy. The results indicated that the carriers were encapsulated by nano-TiO2 with a thickness of 300–450 nm. The main crystalline phase of TiO2 calcined at 650℃ was anatase, and the average grain size was 8.3 nm. The FT-IR absorption bands at 955.38 cm-1 suggested that new chemical bonds among Ti, O, and Si had formed in the composites. The photocatalytic（PC） activity of the composites was investigated under UV irradiation. Furthermore, the photodegradation kinetics of formaldehyde was investigated using the composites as the cores of an air cleaner. A kinetics study showed that the reaction rate constants of the gas-phase PC reaction of formaldehyde were κ = 0.576 mg·m–3·min–1 and K = 0.048 m3/mg.